Vision and Displays for Military and Security Applications The Advanced Deployable Day/Night Simulation Project - Niall, Keith K.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Vision and Displays for Military and Security Applications presents recent advances in projection technologies and associated simulation technologies for military and security applications. Specifically, this book covers night vision simulation, semi-automated methods in photogrammetry, and the development and evaluation of high-resolution laser projection technologies for simulation. Topics covered include: advances in high-resolution projection, advances in image generation, geographic modeling, and LIDAR imaging, as well as human factors research for daylight simulation and for night vision devices. This title is ideal for optical engineers, simulator users and manufacturers, geomatics specialists, human factors researchers, and for engineers working with high-resolution display systems. It describes leading-edge methods for human factors research, and it describes the manufacture and evaluation of ultra-high resolution displays to provide unprecedented pixel density in visual simulation.
Creating Day and Night: Past, Present, and Future -- Development of a DVI-Compatible VGA Projector Engine Based on Flexible Reflective Analog Modulators -- Brightness and Contrast of Images with Laser-Based Video Projectors -- Physics Based Simulation of Light Sources -- Integration of a Deployable CIGI-Based Image Generator in an Existing Simulation -- Advances in Scalable Generic Image Generator Technology for the Advanced Deployable Day/Night Simulation Project -- Detection Threshold of Visual Displacement in a Networked Flight Simulator -- Evaluation of the Spatial and Temporal Resolution of Digital Projectors for use in Full-Field Flight Simulation -- A Spatial Cognition Paradigm to Assess the Impact of Night Vision Goggles on Way-Finding Performance -- Psychophysics of Night Vision Device Halos -- Effects of Screen Resolution and Training Variation on a Simulated Flight Control Task -- Video-to-Reference Image Indexing -- AVS LIDAR for Detecting Obstacles Inside Aerosol.
Keywords: Physics; Computer vision; Geographical information systems; Computer engineering; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Image Processing and Computer Vision; Geographical Information Systems/Cartography.; Electrical Engineering